ARTOCARPUS DIVERSITY IN LOLOAN VILLAGE, NORTH LOMBOK - Nutrinem; Slamet Mardiyanto Rahayu (Nusadaya Journal of Multidiciplinary Studies, 2025)
Lombok is one of the islands in the Lesser Sunda Islands, home to a rich biodiversity, including plants. This research is necessary to determine the diversity of Artocarpus plants in Loloan Village. Research shows that four Artocarpus species are present in Loloan Village: Artocarpus heterophyllus, A. altilis, A. integer, and A. camansi.